Comparative study on the growth performance between indigenous swamp and Murrah crossbred buffaloes - Tingkas, Jaizurah Vera (2017)
The Southeast Asia has been reporting annual reduction in the buffalo population with limited land availability for rearing purposes but the demand for beef has increased as a result of increasing human population. Therefore, enhancement in buffalo productivity was done through genetic improvement with the intention of producing dual-purpose crossbred buffaloes (Swamp x River) both for milk and beef productions. This retrospective study was conducted to compare the growth performance and to determine the benefits of the rearing crossbred compared to swamp buffaloes. The records for both swamp and crossbred buffaloes that were born between 2014 and 2016 were acquired from the Buffalo Breeding and Research Centre, Telupid, Sabah, Malaysia. The animal identification and breed, birth weight, weaning weight and the body weights at three monthly intervals were recorded and analyzed using independent T-test. All calves were weaned at 3 months old and were released into paddocks to graze. Supplemented feed was provided at the rate of 1 kg/animal/day. The average birth weight of crossbred buffaloes was 36.635.18 kg, significantly (p<0.05) higher than the average 34.695.28 kg birth weight of swamp buffaloes. The average pre-weaning daily weight gain for swamp and crossbred buffaloes was 0.73 kg/day and 0.98 kg/day while the average post-weaning daily weight gain was 0.39 kg/day and 0.44 kg/day, respectively. Therefore, the 3-monthly body weights of Murrah crossbred buffaloes were significantly higher (p<0.05) than that of swamp buffaloes until the end of the study at 24 months old. The Murrah crossbred and swamp buffaloes achieved the targeted market weight of 250 kg at 15 and 18 months old, respectively while the targeted breeding weight of 385 kg at 26 and 30 months old, respectively. In conclusion, the Murrah crossbred buffaloes showed faster growth rate and reached targeted market and breeding weights at earlier age than that of swamp buffaloes. Thus, farmers can reduce the rearing cost and earn more profit by selling crossbred buffaloes at an earlier age either for slaughter or rearing purposes.